2015 International Siberian Conference on Control and Communications (SIBCON) 2015
DOI: 10.1109/sibcon.2015.7147162
|View full text |Cite
|
Sign up to set email alerts
|

The performance of multithreshold decoder over fading channels

Abstract: Multithreshold decoders (MTD) for self-orthogonal codes (SOC) are discussed. It's known MTD can provide near optimum decoding with linear complexity only. Bit-error rate performance of MTD in multipath Rayleigh and Rician fading channels is analyzed. Several questions of application of MTD with orthogonal frequency division multiplexing and multipleinput and multiple output technology for improving reliability of communication with unmanned vehicles are discussed. The performance of multithreshold decoders in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is shown that change of a method of computation of weight factors of checks allows to improve significantly characteristics of used codes in case of their decoding by the MPD methods in case of big noise level in case of use of soft modems. It has been shown that in this case the MTD can provide in a Gaussian channel characteristics, on 1, 2-7-1,4 dB better than the "hard" modem [4]. …”
mentioning
confidence: 92%
See 2 more Smart Citations
“…It is shown that change of a method of computation of weight factors of checks allows to improve significantly characteristics of used codes in case of their decoding by the MPD methods in case of big noise level in case of use of soft modems. It has been shown that in this case the MTD can provide in a Gaussian channel characteristics, on 1, 2-7-1,4 dB better than the "hard" modem [4]. …”
mentioning
confidence: 92%
“…The algorithms executing only very simple, uniform and fast operations will appear the cheapest in case of all options of implementation. Earlier, theoretical and application results about multi threshold decoding (MTD) algorithms for binary digital streams in Gaussian channels with a large noise level was considered in [4][5][6]. MTD is a very simple iterative algorithm for error correction.…”
mentioning
confidence: 99%
See 1 more Smart Citation